The Formative Proposal of Ignatian Pedagogy in Higher Education: A Right to Comprehensive Quality Education In The 21st Century University - Mejía-Rosal de Durán, Aura (2022)
The text presents the theoretical discussion of the formative proposal of Ignatian pedagogy in higher education, a seal of commitment to educational spirituality generated from the identity, principles and values ​​of its founder, Saint Ignatius of Loyola, to the common educational project emanating from the Ignatian Pedagogy and the pedagogical proposal for Jesuit higher education, for the education of professionals committed to the country, trained in human, ethical and Christian values, conscientious, competent, committed and compassionate citizens. This view is important for the right to a comprehensive quality education. The documentary analysis carried out consolidates the validity of the formative proposal of Ignatian Pedagogy, a transformative educational-pedagogical model in higher education and the commitment of the Rafael Landívar University to comprehensive quality education. Quality in higher education refers to educational quality standards as a need and right for a change in the 21st century university that establishes the appropriate conditions to promote more student-centered learning and use of innovative teaching methods. This requires curricular and technological adaptations, the need for teacher training, and the reinforcement of skills in students and teachers. The value of pedagogical skills in university teaching pursues the mastery of specific skills and abilities for good teaching performance. In the pedagogical proposal for Jesuit higher education, teaching and research are the center of interest of university policies; research for the creation of knowledge and teaching for its dissemination. In Ignatian Pedagogy these two functions have a special meaning in student learning and teaching performance. The contributions emphasize human formation, didactic application and social commitment. They allow the understanding and value of the formative intentionality of Ignatian pedagogy, the integrality of formation, the didactic concretion, and the formative research processes.